Wage Discrimination Against Women PAUD Teachers - Ismiati, Saptosih; Wafa Azizah, Ersya Aqila (Jurnal Legisci, 2024)
PAUD instructors typically work with a female student body. This is because, from a societal standpoint, women are viewed as kind, meticulous people, making this work appropriate for them. PAUD instructors are entitled to a wage structure that guarantees their economic and social well-being until their earnings are insufficient. In terms of norms, the government has established laws that ensure the rights of all workers; nonetheless, social differences in women's earnings continue to exist. It would, therefore, remain challenging to address the issue of PAUD teachers' low pay if the regulations are set solely by statutory regulations and no steps are taken to ensure its implementation.